2019
DOI: 10.1007/s00426-019-01206-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of episodic retrieval on inhibition in task switching: a diffusion model analysis

Abstract: Inhibition in task switching is inferred from n − 2 task repetition costs: slower response times and poorer accuracy for ABA task switching sequences compared to CBA sequences, thought to reflect the persisting inhibition of task A across an ABA sequence. Much work has examined the locus of this inhibition effect, with evidence that inhibition targets response selection processes. Consistent with this, fits of the diffusion model to n − 2 task repetition cost data have shown that the cost is reflected by lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In such studies, participants switch between simple classification tasks, such as color versus size versus shape of target stimuli, typically using only two different response keys (see Kiesel et al, 2010; Koch et al, 2018; Vandierendonck et al, 2010, for general reviews). Interestingly, recent nonlinguistic studies regarding n−2 repetition costs from Grange et al (e.g., Grange et al, 2017; Kowalczyk & Grange, 2020) suggested that there is also a contribution from feature repetitions across trials, which might lead to interference due to episodic retrieval (see Frings et al, 2020, for a recent review). The episodic retrieval account proposes that during any given trial, all perceptual (e.g., cue and stimulus) and action (i.e., response) representations are stored together in episodic memory.…”
Section: Inhibitory Phenomena In Bilingual Language Productionmentioning
confidence: 99%
“…In such studies, participants switch between simple classification tasks, such as color versus size versus shape of target stimuli, typically using only two different response keys (see Kiesel et al, 2010; Koch et al, 2018; Vandierendonck et al, 2010, for general reviews). Interestingly, recent nonlinguistic studies regarding n−2 repetition costs from Grange et al (e.g., Grange et al, 2017; Kowalczyk & Grange, 2020) suggested that there is also a contribution from feature repetitions across trials, which might lead to interference due to episodic retrieval (see Frings et al, 2020, for a recent review). The episodic retrieval account proposes that during any given trial, all perceptual (e.g., cue and stimulus) and action (i.e., response) representations are stored together in episodic memory.…”
Section: Inhibitory Phenomena In Bilingual Language Productionmentioning
confidence: 99%
“…It is widely assumed that switching from N-2 to N-1 leads to (backward) inhibition of the task-set performed in N-2; when one is required to switch to the same task-set in Trial N, this task-set lays still in an inhibited state, and some extra processing is needed to overcome such inhibition. Therefore, overcoming of lingering inhibition, which is required in N-2 task repetition sequences, is generally thought to give rise to N-2 repetition costs (for an alternative interpretation of N-2 repetition costs, see Grange et al, 2017; Kowalczyk & Grange, 2020).…”
Section: Response-based Strengthening Of Task Setmentioning
confidence: 99%
“…For example, if the stimulus appeared in the bottom left, and the task required horizontal movement, the participant needed to move the stimulus to the bottom right by pressing the button “2.” According to three different movement rules, two task sequences, CB A and AB A , were obtained. Kowalczyk and Grange (2020) found that when task A in trial N-2 appeared again (AB A ), the response time of task A was significantly slower than task A in the CB A sequence.…”
Section: Experimental Paradigmsmentioning
confidence: 94%
“…In the movement direction switching tasks, participants must move the target directionally according to cues that are repeated or switched across trials ( Mayr, 2002 ; Grange, 2018 ; Kowalczyk and Grange, 2020 ). Kowalczyk and Grange (2020) asked the participants to perform a rapid spatial transformation of the stimulus location according to the cues and move the stimulus to the correct location by pressing the key corresponding to the spatial location. The numbers “1,” “2,” “4,” and “5” corresponded to four locations: bottom left, bottom right, top left, and top right, respectively.…”
Section: Experimental Paradigmsmentioning
confidence: 99%